Is sunitinib-induced hypothyroidism a predictive clinical marker for better response in metastatic renal cell carcinoma patients?. (3rd May 2016) - Bozkurt, Oktay; Karaca, Halit; Hacıbekiroglu, Ilhan; Kaplan, Muhammed Ali; Duzkopru, Yakup; Uysal, Mukremin; Berk, Veli; Inanc, Mevlude; Duran, Ayse Ocak; Ozaslan, Ersin; Ucar, Mahmut; Ozkan, Metin
Abstract : Background: The main goal of this study was to examine whether the occurrence of hypothyroidism during sunitinib therapy in patients with metastatic renal cell carcinoma (mRCC) is associated with a better outcome. Methods: The study enrolled 81 patients with pathologically proven mRCC who were treated with sunitinib between March 2008 and June 2013.Thyroid function evaluation comprised (free-thyroxine) FT4 and thyroid-stimulating hormone (TSH) before treatment and at day 1 of each 6-week cycle. Survival analysis was performed using the Kaplan–Meier method, and the differences among the groups were determined using the log-rank test. Results: Hypothyroidism occurred in 30 (37%) of 81 patients within a median 3 months (range 1–18) of treatment initiation. There was a statistically significant correlation between the occurrence of hypothyroidism during treatment and the rate of objective remission (ORR) (hypothyroid patients vs euthyroid patients: 46.7 vs 13.7%, respectively; P  = 0.001). Median progression-free survival (PFS) was 10 (95% CI 6.13–13.8) months in the euthyroid patients, and 17 (95% CI 9.33–24.6) months in the hypothyroid patients ( P  = 0.001). The median overall survival (OS) was 39 (95% CI 25.4–52.5) months in the hypothyroid patients and 20 (95% CI 14.7–25.2) months in the euthyroid patients ( P  = 0.019). Conclusions: The occurrence of hypothyroidism during treatment in patients was significantly associated with longer PFS, OS and better ORR in the current study.